Model Strategi Penguatan Resiliensi Usaha Mitigasi Burnout terhadap Kinerja Finansial dan Kinerja Psikologis Pelaku UMKM - Enny Istanti; Achmad Daengs GS; Ramadhan Kurnia Iman; Mahjudin Mahjudin; Dody Suhermawan; Moch. Rachmanday Firmansyah (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Indonesian MSMEs face high work pressure due to limited capital, market competition, and daily operational demands, which have the potential to trigger burnout and threaten business continuity. This study adopted a quantitative approach with a cross-sectional survey design and employed Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis. The findings are expected to contribute to the development of the Job Demands-Resources (JD-R) model in the context of MSMEs and provide practical insights for improving business resilience. The results indicate that burnout significantly influences business resilience. In addition, both burnout and business resilience have significant effects on the financial and psychological performance of MSMEs. Business resilience also acts as a mediating variable in the relationship between burnout and MSME performance. Thus, the success of MSMEs is not only determined by economic achievements, but also by the ability of business owners to maintain psychological health, optimize resources, build support networks, and respond to changes in the business environment in a flexible, planned, and sustainable manner in the long term more effectively.